Sumpit (Blowgun) as Traditional Weapons with Dayak High Protection - Hamid Darmadi (STKIP Singkawang, 2018)
The Dayak ancestors who live amid lush forests with towering tree trees and inhabited by a variety of wild animals and wild animals, inspire for the Dayak's ancestors to make weapons that not only protect themselves from the ferocity of forest life but also have been able to sustain the existence of their survival. Such living conditions have motivated the Dayak ancestors to make weapons called